Kepatuhan Perawat dalam Melakukan Oral Hygiene di Unit Perawatan Intensif - Musdalipah Musdalipah; Yuliana Syam; Takdir Tahir (Jurnal Keperawatan Silampari, 2021)
This study aims to identify factors that influence nurse compliance and find the best solution to improve adherence to oral hygiene. The research method begins with searching scientific articles in 4 databases, namely PubMed, Wiley, science direct, and google scholar. The results of the study of 7 included articles, 42.85% (3 pieces) stated that nurses' knowledge and perceptions were the main factors that influenced nurse compliance, and 14.3% (1 article) indicated that service practices/facilities affected adherence. Other factors were found including; limited time, motivation, nurse workload, unavailability of oral hygiene procedures, and lack of interprofessional collaboration, so the best solution is to increase the knowledge and competence of nurses with training, workshops, and monitoring systems in the implementation of the VAP bundle. In conclusion, nurses' knowledge and perceptions are the main factors that affect nurse compliance in performing oral hygiene, so increasing knowledge and competence is the best solution as a joint effort to reduce the incidence of VAP. Keywords: VAP Bundle, Compliance, Intensive Care Unit, Oral Hygiene